Genotoxic and cytotoxic evaluation of the herbicide flurochloridone on Chinese hamster ovary (CHO-K1) cells - Nikoloff, Noelia (2012)
The in vitro effects of flurochloridone (FLC) and its formulations Twin Gold Pack® (25% a.i.) and Rainbow® (25% a.i.) were evaluated on Chinese hamster ovary (CHO-K1) cells by genotoxicity [sister chromatid exchange (SCE)] and cytotoxicity [cell-cycle progression, proliferative rate index (PRI), mitotic index (MI), MTT, and neutral red] end points. Cells were treated for 24. h within the 0.25-15 μg/ml concentration range. FLC and Twin Pack Gold® induced a significant and equivalent increase in SCEs regardless of the concentration. Rainbow®-induced SCEs at concentrations higher than 2.5 μg/ml; however, the increases were always lower than those induced by FLC and Twin Pack Gold®. For all compounds, the PRI decreased as a function of the concentration titrated into cultures. Whereas only the highest FLC and Twin Pack Gold® concentrations induced a significant reduction of the MI, all tested Rainbow® concentrations induced MI inhibition. Overall, the results demonstrated that although all compounds were not able to reduce the lysosomal activity, the mitochondrial activity was diminished when the highest concentrations were employed. These observations represent the first study analyzing the genotoxic and cytotoxic effects exerted by FLC and two formulated products on mammalian cells in vitro, at least on CHO-K1 cells.